An evolutionary approach to hypnotizability. Issue 4 (12th April 2021) - Santarcangelo, Enrica L.; Carli, Giancarlo; Sebastiani, Laura
ABSTRACT: We propose here an evolutionary interpretation of the presence of highly hypnotizable persons (highs) among the general population. Current experimental evidence suggests the presence of stronger functional equivalence between imagery and perception, non-opioid cognitive control of pain, favorable cardiovascular asset, and greater interoceptive sensitivity in highs. We hypothesize that these characteristics were greatly relevant to our ancestors' survival, and that they may have facilitated the natural selection of individuals who are now named "highs" due to one of their side effects – the proneness to accept suggestions – as part of the reported physiological features. Unfortunately, our theoretical hypothesis cannot be currently experimentally proven. We believe, however, that looking at hypnotizability in a naturalistic, evolutionary perspective may emphasize the importance of its physiological correlates in daily life and in the prediction of the outcome of medical treatments.